1995
DOI: 10.1172/jci118374
|View full text |Cite
|
Sign up to set email alerts
|

A new subgroup of lectin-bound biliary proteins binds to cholesterol crystals, modifies crystal morphology, and inhibits cholesterol crystallization.

Abstract: Biliary proteins inhibiting or promoting cholesterol crystallization are assumed to play a major role in cholesterol gallstone pathogenesis. We now report a new group of biliary proteins that bind to cholesterol crystals, modify crystal morphology, and inhibit cholesterol crystallization. Various glycoprotein mixtures were extracted from abnormal human gallbladder bile using lectin affinity chromatography on concanavalin A, lentil, and Helix pomatia columns and were added to supersaturated model bile. Independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 45 publications
0
21
0
1
Order By: Relevance
“…We speculate that crystal growth inhibitors like biliary IgA attach to the most rapidly growing sites l i k e s p i r a l a n d e d g e d i s l o c a t i o n s o n t h e thermodynamically stable monohydrate crystals, thus changing crystal morphology, retarding crystal growth and decreasing final crystal concentration [19] . This concept applies to many crystal growth inhibitors in biomineralization.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We speculate that crystal growth inhibitors like biliary IgA attach to the most rapidly growing sites l i k e s p i r a l a n d e d g e d i s l o c a t i o n s o n t h e thermodynamically stable monohydrate crystals, thus changing crystal morphology, retarding crystal growth and decreasing final crystal concentration [19] . This concept applies to many crystal growth inhibitors in biomineralization.…”
Section: Discussionmentioning
confidence: 98%
“…To remove insoluble constituents, bile samples were ultracentrifuged at 100 000 × g for 1h. Biliary protein fractions were isolated by affinity chromatography using -Concanavalin A and Helix pomatia-lectin, as described [19,20] . Biliary IgA was isolated from the bound protein fraction by immunoaffinity chromatography [20] .…”
Section: Chemicals and Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the association between serum lipids and gallstones has remained controversial, decreased HDL cholesterol and increased triglyceride levels might be correlated with biliary cholesterol supersaturation and the risk for cholelithiasis (14)(15)(16). Previous studies have indicated that the interaction of sustained cholesterol supersaturation in bile with biliary proteins, such as mucins, modulates cholesterol crystallization and gallstone formation (1)(2)(3)(4)(17)(18)(19). Together, these findings suggest that abnormalities in cholesterol and lipoprotein metabolism play an important role in the pathogenesis of cholesterol cholelithiasis.…”
mentioning
confidence: 99%
“…The results of these studies indicated that added immunoglobulins (6,17), cr 1 -acid glycoprotein (7), aminopeptidase N (818) and haptoglobin (19) promote cholesterol crystallization in model biles. In addition to crystallization-promoting proteins, inhibitors have been isolated from CABF (3,4,20,21).…”
mentioning
confidence: 99%